183k views
2 votes
Find the product to each problem

(2x - 4y)(x + 3y) =
(x − 4)(2x − 1) =
(2x - 3)(x - 1) =
(3x - 3y)(2x - y) =

1 Answer

5 votes

Answer:

Explanation:

To find the product of each expression, we can use the distributive property to expand the terms:

(2x - 4y)(x + 3y) = 2xx + 2x3y - 4yx - 4y3y

= 2x^2 + 6xy - 4xy - 12y^2

= 2x^2 - (-2xy - 12y^2)

= 2x^2 - 2xy - 12y^2

(x − 4)(2x − 1) = x2x + x(-1) - 42x - 4(-1)

= 2x^2 - x - 8x + 4

= 2x^2 - 9x + 4

(2x - 3)(x - 1) = 2xx + 2x(-1) - 3x - 3(-1)

= 2x^2 - x - 3x + 3

= 2x^2 - 4x + 3

(3x - 3y)(2x - y) = 3x2x + 3x(-y) - 3y2x - 3y(-y)

= 6x^2 - 3xy - 6xy - 3y^2

= 6x^2 - (-6xy - 3y^2)

= 6x^2 - 6xy - 3y^2

I hope this helps! Let me know if you have any questions.

User Dabs
by
5.2k points